Function and Distribution of 5-HT(2) Receptors in the Honeybee (Apis mellifera) - Thamm, Markus (Public Library of Science, 2013)
BACKGROUND: Serotonin plays a pivotal role in regulating and modulating physiological and behavioral processes in both vertebrates and invertebrates. In the honeybee (Apis mellifera), serotonin has been implicated in division of labor, visual processing, and learning processes. Here, we present the cloning, heterologous expression, and detailed functional and pharmacological characterization of two honeybee 5-HT(2) receptors. METHODS: Honeybee 5-HT(2) receptor cDNAs were amplified from brain cDNA. Recombinant cell lines were established constitutively expressing receptor variants. Pharmacological properties of the receptors were investigated by Ca(2+) imaging experiments. Quantitative PCR was applied to explore the expression patterns of receptor mRNAs. RESULTS: The honeybee 5-HT(2) receptor class consists of two subtypes, Am5-HT(2α) and Am5-HT(2β). Each receptor gene also gives rise to alternatively spliced mRNAs that possibly code for truncated receptors. Only activation of the full-length receptors with serotonin caused an increase in the intracellular Ca(2+) concentration. The effect was mimicked by the agonists 5-methoxytryptamine and 8-OH-DPAT at low micromolar concentrations. Receptor activities were blocked by established 5-HT receptor antagonists such as clozapine, methiothepin, or mianserin. High transcript numbers were detected in exocrine glands suggesting that 5-HT(2) receptors participate in secretory processes in the honeybee. CONCLUSIONS: This study marks the first molecular and pharmacological characterization of two 5-HT(2) receptor subtypes in the same insect species. The results presented should facilitate further attempts to unravel central and peripheral effects of serotonin mediated by these receptors.